A new species of the genus Wadithamnus (Amaranthaceae, Achyranthoid) from north-eastern Somalia - Baldesi, Giacomo (Phytotaxa, 2024)
A new species of the hiterto monotypic genus Wadithamnus is described as new to science from two herbarium specimens housed at B and FT, collected in 1989 by B. Gabriel in Somalia, it is endemic to north-eastern Somalia and known so far only from the type collection.